Does Axial Length Influence the Dose Effect of Horizontal Strabismus Surgery? - Uecelehan, Hatice; Palmowski-Wolfe, Anja (Klinische Monatsblätter für Augenheilkunde, 2025)
Background Dose effect (DE) of strabismus surgery is thought to decrease with increasing axial length (AL), and it has been suggested that this effect may be more important in hyperopes over + 2 D. Here, we analyse the influence of AL on the DE of horizontal strabismus surgery in regard to its clinical relevance.Methods Retrospective chart analysis of patients who had undergone horizontal strabismus surgery between 2020 and 2023. Statistical analysis: descriptive analysis and ANOVA (R 4.1.2).Results There were 65 patients (34 male and 31 female) included; mean age: 18.0 years (range 5 – 74). Mean AL was 23.50 mm (range: 20.80 – 28.50 mm). At the 3-month follow-up, 83.1% of patients demonstrated binocularity. Mean DE was 2.36 PD/mm at distance and 2.60 in near vision. There was no significant influence of AL on the DE of surgery (p = 0.30). However, DE was significantly higher in esotropia (n = 32) than exotropia (n = 33) in distant and near vision (p = 0.0 000 403) and in both groups, patients with positive binocularity had a significantly greater DE than patients without binocularity (p = 0.0032).Conclusion Our data showed no significant correlation between AL and the DE of surgery, while the type of strabismus and binocularity had a significant influence on the DE of surgery. However, AL is still important for surgical planning, in particular, to assess the risk of a deviating muscle path or thin sclera in high myopia.
Keywords: axial length; dose effect; horizontal strabismus surgery; esotropia; exotropia; strabismus; pediatric ophthalmology; neuro-ophthalmology